Analysis of Facial Deformities in Korean Leprosy - Kim, Ji Heui (Korean Society of Otorhinolaryngology-Head and Neck Surgery, 2013)
OBJECTIVES: The clinical features of various facial deformities in Korean leprosy patients were evaluated according to the type of leprosy. METHODS: One hundred ninety six patients with leprosy were examined for various facial deformities using a nasal speculum, endoscope, and digital camera. The frequency and severity of external nasal deformities and septal perforations were evaluated according to the type of leprosy. Eye deformities, ear deformities, and facial palsy were also assessed. RESULTS: Seventy-one patients (36.2%) displayed external nasal deformities: 28 minimal contractures, three cartilage contractures, two bony-cartilage contractures, and 38 skin defects. The external nasal deformity and severe form deformity in lepromatous types were more frequent compared to other types (P<0.05 for each variable). Twenty-three patients (9%) displayed septal perforations, among whom 11 had cartilaginous perforations and 12 had bony-cartilaginous perforations. The frequency of septal and bony-cartilaginous perforations did not differ significantly between the types of leprosy (P>0.05 for each variable). Sixty-one patients (31.1%) had eye deformities and 19 patients (9.7%) had facial nerve palsy, common in the borderline type. No cases of ear deformities were observed. CONCLUSION: Korean patients had characteristic deformities according to the type of leprosy. They were different from those seen in the prior analyses of Caucasian populations.